Epidemiological and antibiotic susceptibility pattern of bacterial paronychial infection - Javed, Bilal; Taj, Muhammad Kamran; Khan, Masroora Ali; Akram, Aroosa (Journal of the Pakistan Medical Association, 2026)
Objective: To identify the bacterial aetiology of paronychia, and assess the antibiotic resistance patterns of the isolated pathogens. Method: The cross-sectional cohort study was conducted from December 1, 2021, to December 31, 2022, at the Department of Microbiology, Centre for Advanced Studies in Vaccinology and Biotechnology, Quetta, Pakistan, and comprised samples collected from Bolan Medical Complex Hospital, Quetta, and Sandeman Provisional Hospital, Quetta, of patients clinically diagnosed with paronychia. Organisms were isolated using selective and differential media, and they were categorised by using biochemical tests, antimicrobial susceptibility test and polymerase chain reaction. Data was analysed using SPSS 26. Results: Of the 480 samples collected, 212(44.16%) were positive; 160(33.3%) females and 52(10.83%) males. The most affected age group was 20-30 years 70(14.56%). Among the positive samples, 90(18.75%) were identified as staphylococcus aureus, followed by staphylococcus. epidermidis 50(10.41%), pseudomonas aeruginosa 42(8.75%) and klebsiella pneumoniae 30(6.25%). Staphylococcus aureus and staphylococcus epidermidis were found resistant to ceftriaxone and amoxicillin, while pseudomonas aeruginosa was resistant against sulfamethoxazole and vancomycin, and klebsiella pneumoniae was resistant to doxycycline and vancomycin. Conclusion: Staphylococcus aureus was the predominant pathogen in bacterial paronychia, with higher prevalence among females and young adults. Besides, high levels of antibiotic resistance was noted. Key Words: Paronychia, Antibiotic resistance, Staphylococcus aureus, Pseudomonas aeruginosa, Epidemiology.